Use of resin-encrusted arthropods as a didactic tool for teaching and learning Biology (Research, Society and Development, 2023)
The technique of encrusting arthropods can be used in the production of didactic material so that students can concretely visualize the external morphological differences between arthropod species and their classification. With the use of this material produced through this technique, combined with an expository class, we sought to achieve greater efficiency in the teaching-learning process with students in the third year of high school. First, a diagnostic evaluation was carried out, requiring the students to answer a questionnaire, where data were collected about what they knew about the external morphology of arthropods before the intervention. After that, there was a class with the use of arthropods encrusted in resin and the handling of the specimens by the students. In the end, they answered the same questionnaire again to assess the variation in errors and correct answers. It can be confirmed the effectiveness of using didactic material built from the inlay technique, as a learning facilitator, so that students could understand arachnids, millipedes, and centipedes, seeking to understand the external morphological characteristics, the function of the structures and the role that these different species play in the environment, all in a practical, creative, dynamic and interactive way.